Sleep Quality Improvement of Benign Prostate Hyperplasia Patients After Transuretral Resection of Prostate - Alice Agustine; Marta Hendry (Sriwijaya Journal of Surgery, 2018)
ABSTRACT Introduction. Nocturia is lower urinary tract symptoms on benign prostat hyperplasia patients that made him asleep at night to urinate. This condition impacted on many level of patient life, which are quality of life, quality of sleep, daytime function, morbidity and mortality and nocturia has the biggest impact on patient sleep quality. Methods. This is an observational study including 30 patient of benign prostat hyperplasia undergoing transurethral resection of the prostate as research subjects. All patient were assessed using the Pittsburgh sleep quality index and international prostate symptom score at baseline and 2 month after transuretral resection of the prostate Results. A total 23 patients (76,7%) had a sleep disorder as a score of 5 or more on Pittsburgh sleep quality index score. After the transurethral resection of the prostate, pittsburgh sleep quality index score of 12 patient have decreased (less than 5) and 11 others with persistent sleep disorder. Pittsburgh sleep quality index significantly decreased after transurethral resection of the prostate from ±9,36 to ±5,03 (p-value 0,000). Nocturia also significantly decreased after transuretral resection of the prostate from ±3,46 to ±2,40 (P value 0,003). Lower urinary track symptoms in this patient also getting better after surgery. The international prostat symtoms score decreased after transurethral resection of the prostat from ±21,80 to ±7,67 with P value 0,000 Conclusion. Transuretral resection of prostate improves sleep quality dan decreased lower urinary track symptoms in benign prostate hypertrophy patients.